The Efficiency and Performance of Apple’s Supply Chain Management - Budiono, Kevin; Ellitan, Lena (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
The success of companies is significantly shaped by the efficiency and effectiveness of supply chain management in the dynamic realm of global commerce. Apple Inc. is at the top of this complex supply and demand dynamic in international business management. Apple, as the market leader, is well-known for its supply chain capabilities as well as groundbreaking innovations in technology. This paper aims to explore Apple Inc.’s advanced supply chain management network, showing how it has contributed to the company's extraordinary success and how it translates into building a market competitive advantage. Apple maintains a strong market position by continually improving its supply chain performance, as evidenced by its expanding gross margin and negative cash-to-cash cycle, which are indicators of both successful cash management and high market demand. Overall, Apple's supply chain journey serves as a model for other companies that seek quality, innovation, and long-term competitiveness. Companies can overcome hurdles and position themselves as market leaders by embracing strategic fit and prioritizing consumer satisfaction. Apple's supply chain success demonstrates the value of optimal management and strategic alignment in the ever-changing global business.